Енергозбереження та енергоефективність в домогосподарствах населення - Болтянська, Лариса Олексіївна; Boltianska, Larysa (Запоріжжя : 2022, 2022)
UA: В статті висвітлені основні аспекти теоретичних понять «енергозбереження» та «енергоефективність». Енергоефективність – це галузь знань, що знаходиться на стику інженерії, економіки, юриспруденції та соціології. Термін розкриває розумне вживання енергетичних ресурсів, досягнення економічно ефективності використання наявних паливно-енергетичних ресурсів при відповідному рівні розвитку техніки та технології з дотриманням вимог до навколишнього середовища. «Енергозбереження» як будь-яке «збереження або заощадження» є процесом заощадження енергії, у ході якого скорочується потреба в енергетичних ресурсах. Результатом цього процесу є економія енергоресурсів за нормальних режимах будь якої діяльності. Вітчизняні домогосподарства залишаються найбільшими споживачами енергоносіїв. Проте, постійне зростання цін на енергоресурси спричиняє зниження платоспроможності суб’єктів господарювання, призводить до енергетичної бідності. Найбільш ефективний спосіб зниження витрат на електроенергію для споживача – це зниження рівня її споживання, або використання альтернативних джерел енергії. Для економії на опаленні доконче потрібно правильне комбінування і управління джерелами тепла, що дозволить істотно скоротити витрати на опалення приватного будинку, забезпечити господарські потреби та отримати додаткове джерело поповнення родинного бюджету. EN: The article highlights the main aspects of the theoretical concepts of "energy saving" and "energy efficiency". Energy efficiency is a field of knowledge at the intersection of engineering, economics, jurisprudence and sociology. The term reveals the reasonable use of energy resources, the achievement of economic efficiency in the use of available fuel and energy resources at the appropriate level of development of equipment and technology in compliance with environmental requirements. The concept of "energy efficiency" is revealed through the achievement of a certain result, in particular, heating the house, using a smaller amount of energy than is usually required. "Energy conservation" as any "conservation or savings" is a process of saving energy, during which the need for energy resources is reduced. It is associated with extensive energy consumption in the context of the implementation of the energy saving regime, which describes the quantitative characteristics. The result of this process is the saving of energy resources under normal operating modes of the enterprise. Domestic households remain the largest consumers of energy carriers. However, the constant increase in prices for energy resources causes a decrease in the solvency of economic entities and leads to energy poverty. The main criterion for the level of energy poverty is the threshold value – the maximum conceivable share of the household's income that is spent on paying for energy consumption. The most effective way to reduce electricity costs for the consumer is to reduce the level of its consumption or use alternative energy sources. It is also important to realize that using other heat sources for your own needs is not the only way to save gas and eliminate dependence on it. It is necessary to ensure the growth of the overall energy efficiency of the building: identify and eliminate all heat leaks, use heat more rationally, and minimize the heat loss of the building. To save on heating, you absolutely need the correct combination and management of heat sources, which will allow you to significantly reduce the costs of heating a private house, provide for household needs and get an additional source of replenishment of the family budget.
Energy saving and energy efficiency in households
Болтянська Л. О. Енергозбереження та енергоефективність в домогосподарствах населення. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 78-91.
Keywords: енергозбереження; енергоефективність; домогосподарства; енергетична бідність; джерела фінансових ресурсів домогосподарств; альтернативні джерела опалення; сонячні технології; пелети; energy saving; energy efficiency; households; energy poverty; sources of household financial resources; alternative sources of heating; solar technologies; pellets